Pengaruh Model Pembelajaran Connecting Organizing Reflecting Extending (CORE) Terhadap Kemampuan Mengulas Karya Fiksi Siswa SMP Negeri 8 Gunungsitoli - Zebua, Yogi; Bawamenewi, Arozatulo; Bu'ulolo, Yanida; Riana, Riana (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of the study was to determine the effect of Connecting Organizing Reflecting Extending (CORE) learning model on the ability to review fiction works of junior high school students. This type of research is quantitative research with experimental method. The research subjects were students of class VIII-A of SMP Negeri 8 Gunungsitoli in even semester totaling 31 students and class VIII-B of SMP Negeri 8 Gunungsitoli in even semester totaling 27 students. This research instrument is in the form of tests, namely pretest and posttest. Data collection techniques are tests, observation sheets, and documentation. Data analysis techniques involve normality tests, homogeneity tests, and hypothesis tests. Based on the results of the posttest (final test) in the control class with 27 students obtaining an average score of 62 and the posttest results in the experimental class (trial class) with 31 students obtaining an average score of 78. Based on the research results, there is an influence of the Connecting, Organizing, Reflecting, Extending (CORE) learning model on the ability of eighth grade students to review fiction works at UPTD SMP Negeri 8 Gunungsitoli. It can be concluded that with the Connecting Organizing Reflecting Extending (CORE) learning model, there is an impact on the ability to review fiction works of students in the eighth grade at SMP Negeri 8 Gunungsitoli in the 2024/2025 academic year.